IMPROVING ORAL HYGIENE STATUS IN CHILDREN WITH AUTISM SPECTRUM DISORDER IN BANDUNG THROUGH EDUCATION USING “TOOTH BRUSHING VISUAL PEDAGOGY” FLIPCHART - Josevinda Ayu Pramesti; Sri Susilawati; Inne Suherna Sasmita (Jurnal Health Sains, 2023)
Background: Autism Spectrum Disorder (ASD) is characterized by social communication deficits and restricted interests. Children with ASD face challenges in oral health, necessitating education. Education with visual pedagogy using “Tooth Brushing Visual Pedagogy” flipchart can be used to improve dental health in ASD children. Purpose: This study examined the effectiveness of the "Tooth Brushing Visual Pedagogy" flipchart in improving oral hygiene among children with ASD at Biruku Indonesia Foundation. Methods: A quasi-experimental study with 14 participants measured the Patient Hygiene Performance (PHP) plaque index pre- and post-education. The flipchart was used, followed by a toothbrushing session Results: A significant improvement (p < 0.05) was observed (p-value = 0.000071). Before education, plaque index varied from excellent (0.0%) to poor (21.42%). After education, excellent and good oral hygiene increased (0.0% and 71.42%, respectively), while fair and poor levels decreased (28.57% and 0.0%, respectively). Conclusion: The "Tooth Brushing Visual Pedagogy" flipchart effectively improved oral hygiene among children with ASD.